Pengaruh Kualitas Produk Dan Kemasan Terhadap Keputusan Pembelian - Muchamad Azis Alfayed Azis; Leny Muniroh; M. Imam Sundarta (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This research discusses how product quality and packaging influence purchasing decisions. This research aims to determine the influence of product quality and packaging on purchasing decisions at the Maharaja Super Cake shop, East Jakarta. The data collection technique used a questionnaire method with 100 respondents who were customers of the Maharaja Super Cake shop. The analysis carried out was validity, reliability, classical assumptions, multiple linear regression, correlation test, determination test, t-test and F-test using the SPSS 25 test tool. The results of this research show that product quality has a positive and significant effect on purchasing decisions, packaging has an effect positive and significant on purchasing decisions, product quality and packaging has a positive and significant effect on purchasing decisions.